Odpowiedzi

Najlepsza Odpowiedź!
2009-11-14T22:12:03+01:00
X² (x -12) + 4(x-12)=0
(x-12)(x²+4)=0
x=12
x²=-4 sprzecznosc

x³-9x²+23x-15=0

P.S. chyba blednie przepisales bo musi byc 4x a nie 44x...


x³-9x²+23x-15=0
metoda Hornera

1 -9 23 -15
1 1 -8 15 0 --> x² - 8x + 15

x² - 8x + 15=0
Δ=64-4*1*15
Δ=4
√Δ=2
x1=8-2/2 = 3
x2=8+2/2 = 5

pzdr ;)
2009-11-14T23:01:17+01:00
X² (x -12) + 4(x-12)=0
(x-12)(x²+4)=0
x=12
x²=-4 sprzecznosc

x³-9x²+23x-15=0


x³-9x²+23x-15=0

1 -9 23 -15
1 1 -8 15 0 --> x² - 8x + 15

x² - 8x + 15=0
Δ=64-4*1*15
Δ=4
√Δ=2
x1=8-2/2 = 3
x2=8+2/2 = 5